Downregulation of p53 by Insufficient CTCF in CD4+ T Cells Is an Important Factor Inducing Acute Graft-Versus-Host Disease - Hua, Juan; Chen, Yan; Fu, Bin; Chen, Xu; Xu, Xue-jun; Yang, Shuang-Hui; Chen, Cong; Xu, Ya-jing (Frontiers in Immunology, 2020)
p53 suppresses inflammatory and autoimmune diseases by inhibiting the inappropriate production of pro-inflammatory factors such as IL-1, IL-6, IL-12, and TNF. In addition, p53 plays an important role in regulating Th17/Treg balance. Accumulating evidence suggests that the imbalance of Th17 cells and Tregs is an important cause of aGVHD. However, whether abnormal p53 expression participates in the development of aGVHD remains unclear. In this study, we demonstrated that p53 was downregulated in CD4+ T cells from patients with aGVHD compared with the non-aGVHD group. Furthermore, we confirmed that low expression of CTCF in CD4+ T cells from aGVHD cases is an important factor affecting histone H3K9/K14 hypoacetylation in the p53 promoter and p53 downregulation. Restoring CTCF expression in CD4+ T cells from aGVHD patients increased p53 amounts and corrected the imbalance of Th17 cells/Tregs. Taken together, these results provide novel insights into p53 downregulation in CD4+ T cells from aGVHD patients.